2014
DOI: 10.3389/fpls.2014.00599
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis of male and female flowers of monoecious Quercus suber

Abstract: Monoecious species provide a comprehensive system to study the developmental programs underlying the establishment of female and male organs in unisexual flowers. However, molecular resources for most monoecious non-model species are limited, hampering our ability to study the molecular mechanisms involved in flower development of these species. The objective of this study was to identify differentially expressed genes during the development of male and female flowers of the monoecious species Quercus suber, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 126 publications
(139 reference statements)
6
58
0
1
Order By: Relevance
“…15,000 nematodes as previously described39. A fraction of 2.0 μg was used as starting material for cDNA synthesis using the MINT cDNA synthesis kit (Evrogen), where a strategy based on SMART double stranded cDNA synthesis was applied40. cDNA was quantified by fluorescence and sequenced in a half a plate of the 454 GS-FLX Titanium system, according to the standard manufacturer’s instructions (Roche-454 Life Sciences).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,000 nematodes as previously described39. A fraction of 2.0 μg was used as starting material for cDNA synthesis using the MINT cDNA synthesis kit (Evrogen), where a strategy based on SMART double stranded cDNA synthesis was applied40. cDNA was quantified by fluorescence and sequenced in a half a plate of the 454 GS-FLX Titanium system, according to the standard manufacturer’s instructions (Roche-454 Life Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…Sequence processing assembly and annotation was performed as previously described40. Prior to the assembly of sequences, the raw reads were processed in order to remove sequences with less than 100 nucleotides and low-quality regions.…”
Section: Methodsmentioning
confidence: 99%
“…Within a national initiative, a Portuguese consortium was created to study cork oak ESTs and thus develop a new genomic resource for studying Q. suber (Pereira-Leal et al 2014). This achievement has been used to better understand processes related with plant development (Rocheta et al 2014;Teixeira et al 2014) and adaptation responses to both biotic (Sebastiana et al 2014) and abiotic factors (Magalhães et al 2016). The global overview of up-and downregulated genes in cork oak roots following inoculation with the P. tinctorius resulted in a better insight of those molecular events that control ECM symbiosis (Sebastiana et al 2014).…”
Section: Advances For Mediterranean Fagaceae Ecm Studiesmentioning
confidence: 99%
“…The previous studies indicated that the genes involved in the hormone signaling may play important roles in plant sex determination (Chandler, 2011). In recent years, several different transcriptome analyses showed that numerous hormone-related genes were differently expressed between different flower types, which further indicated hormones had roles in the sexual differentiation and development of floral organ (Wu et al, 2010; Ramos et al, 2014; Rocheta et al, 2014; Sobral et al, 2016). For example, auxin enjoyed a critically regulatory function in the process of floral growth and development in plants (Aloni et al, 2006; Cheng and Zhao, 2007).…”
Section: Discussionmentioning
confidence: 99%